Difficult Perspectives for Polish Foreign Policy – A Report from the Fourth National Political Science Congress (Economic and Political Thought, 2019)
This article is in fact a report from the discussion panel organised on18 September 2018 during the Fourth National Political Science Congressentitled The State in Times of Change. As part of the Congress, ProfessorJózef M. Fiszer from the Institute of Political Studies of the Polish Academyof Sciences, organised an interesting panel entitled ‘Poland’s Foreign Policyin Times of Change in Europe and the World in the Twenty-First Century:Directions, Goals, Forms, Opportunities and Threats’. Panellists, outstandingspecialists, who took part in it discussed goals, tasks, opportunities and threatsfor Polish foreign policy in the twenty-first century. During the discussionnumerous interesting, theoretically and practically significant theses andhypotheses were formulated. They are presented and analysed in this article.
Keywords: Polish foreign policy, NATO, European Union, threats, migration crisis